ANALISIS KINERJA BISNIS UMKM PEMBUDIDAYAAN IKAN LELE DI KECAMATAN TABANAN PADA PANDEMI COVID-19 - Made Putri Ariasih; Ni Luh Laksmi Rahmantari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to analyze the effect of innovation ability and market orientation on the business performance of catfish SMEs in Tabanan District during the pandemic. Innovation capability is measured through product innovation, process innovation, market innovation and service innovation, while company performance is measured through the perspective of sales growth, asset growth and profit growth. The population used was catfish SMEs in the Tabanan District which were still active during the pandemic and were obtained with a sample of 31 respondents. The data that has been collected is then analyzed using Smart PLS version 3. The results show that the ability to innovate positively affects the business performance of catfish SMEs in Tabanan District. Likewise, market orientation also affects the business performance of catfish SMEs in Tabanan District.